Recruitment Techniques and Strategies in a Community-Based Colorectal Cancer Screening Study of Men and Women of African Ancestry. Issue 3 (May 2018) - Davis, Stacy N.; Govindaraju, Swapamthi; Jackson, Brittany; Williams, Kimberly R.; Christy, Shannon M.; Vadaparampil, Susan T.; Quinn, Gwendolyn P.; Shibata, David; Roetzheim, Richard; Meade, Cathy D.; Gwede, Clement K.
Abstract : Background: Recruiting ethnically diverse Black participants to an innovative, community-based research study to reduce colorectal cancer screening disparities requires multipronged recruitment techniques. Objectives: This article describes active, passive, and snowball recruitment techniques, and challenges and lessons learned in recruiting a diverse sample of Black participants. Methods: For each of the three recruitment techniques, data were collected on strategies, enrollment efficiency (participants enrolled/participants evaluated), and reasons for ineligibility. Results: Five hundred sixty individuals were evaluated, and 330 individuals were enrolled. Active recruitment yielded the highest number of enrolled participants, followed by passive and snowball. Snowball recruitment was the most efficient technique, with enrollment efficiency of 72.4%, followed by passive (58.1%) and active (55.7%) techniques. There were significant differences in gender, education, country of origin, health insurance, and having a regular physician by recruitment technique ( p < .05). Discussion: Multipronged recruitment techniques should be employed to increase reach, diversity, and study participation rates among Blacks. Although each recruitment technique had a variable enrollment efficiency, the use of multipronged recruitment techniques can lead to successful enrollment of diverse Blacks into cancer prevention and control interventions.